SYNTHESIS OF NEURAL NETWORK STRUCTURE FOR THE ANALYSIS OF COMPLEX STRUCTURED OCULAR FUNDUS IMAGES - Tatarkanov, Aslan; Alexandrov, Islam; Glashev, Rasul (Journal of Applied Engineering Science, 2021)
This paper proposes an algorithm for synthesizing a neural network (NN) structure to analyze complex structured, low entropy, ocular fundus images, characterized by iterative tuning of the adaptive model’s solver modules. This algorithm will assist in synthesizing models of NNs that meet the predetermined characteristics of the classification quality. The relevance of automating the process of ocular diagnostics of fundus pathologies is due to the need to develop domestic medical decision-making systems. Because of using the developed algorithm, the NN structure is synthesized, which will include two solver modules, and is intended to classify the dual-alternative information. Automated hybrid NN structures for intelligent segmentation of complex structured, low entropy, retinal images should provide increased efficiency of ocular diagnostics of fundus pathologies, reduce the burden on specialists, and decrease the negative impact of the human factor in diagnosis.
Keywords: artificial neural networks; synthesis algorithm; complex structured images; diagnosis of ocular fundus pathologies; automation of non-invasive diagnostics